Legal Politics of Instruments for Punishing Corruptors Based on the Draft Law on Asset Confiscation - Muhammad Nur Khaliq (al-Afkar, Journal For Islamic Studies, 2025)
This research addresses the gap between criminal law policies for corruptors andthe implementation of the Asset Forfeiture Law in Indonesia. Although legal regulations have been established, their implementation remains suboptimal, particularly regarding the recovery of assets illegally obtained by corrupt individuals. Several factors, such as slow legal processes, weak law enforcement, and political instability, hinder the effectiveness of corruption eradication. This highlights the need for reforms in the legal system and law enforcement in Indonesia to ensure a more just and efficient process. This study adopts a normative juridical approach by combining three methods: the Legislative Approach, the Philosophical Approach, and the Asset Forfeiture Ownership Approach in Islamic law. These approaches aim to provide a comprehensive understanding of the legal, moral, and religious aspects of asset forfeiture and its implications within the context of modern law. Through this exploration, the research is expected to offer solutions to existing problems while recommending legal reforms to enhance the effectiveness of corruption eradication in Indonesia.